The prognostic impact of human epidermal growth factor receptor 2 status in metastatic colorectal cancer - Karen Bartley; Jeremy Snider; Cheryl Cho-Phan; Jingru Wang; Peter Martin; Cyndy Simon; Edward Neuberger; Naureen Starling (Future Science OA)
Aim This study evaluated the prognostic impact of human epidermal growth factor receptor 2 (HER2) status on real-world overall survival (rwOS) in patients with metastatic colorectal cancer (mCRC) who had not received HER2-targeted therapy.Methods This retrospective cohort analysis included patients diagnosed with mCRC from a US-based deidentified clinicogenomic CRC database between January 1, 2011, and March 31, 2023. Patients were evaluated based on HER2 status (HER2+ defined as documented ERBB2 amplification). Patient characteristics were assessed at baseline, and rwOS was assessed from start of first-line therapy.Results Among 7121 patients included in the study, 6948 (97.6%) had HER2− mCRC, and 173 (2.4%) had HER2+ mCRC. A higher number of HER2− patients had KRAS mutations (50.7% vs 19.1%) and microsatellite instability-high tumors (3.8% vs 0.6%) than HER2+ patients, while more HER2+ patients received first-line anti–epidermal growth factor receptor therapies (16.8% vs 8.1%). Median (95% CI) rwOS was 29.6 (28.8–30.3) months for HER2− and 30.6 (24.4–38.5) months for HER2+ (unadjusted HR [95% CI], 1.02 [0.84–1.24]; adjusted HR [95% CI], 1.17 [0.96–1.43]).Conclusion HER2 status did not appear to impact rwOS. The findings from this study do not support a prognostic role for HER2 status in mCRC.